Clinical correlates of loss of insight in bipolar depression - Silva,Rafael de Assis da (2017)
Abstract Introduction Affective state may influence insight, especially regarding mania. Nevertheless, studies have so far suggested that depression seems not to significantly impair insight. To the best of our knowledge, this study pioneers the evaluation of how insight variations in bipolar depression correlate with clinical variables. Method A group of 165 bipolar patients, 52 of whom had depressive episodes according to DSM-5 criteria, were followed during a year. All patients underwent clinical assessment, and insight was evaluated through the Insight Scale for Affective Disorders (ISAD). Repeated-measures ANOVA was calculated comparing scores on the four ISAD factors (insight into symptoms, the condition itself, self-esteem and social relationships) in order to investigate differences in insight according to different objects. Correlational analysis explored which clinical symptoms were linked to reduced insight. Results Worse total insight correlated with suicide attempt/ideation and fewer subsyndromal manic symptoms such as mood elevation, increased energy and sexual interest. Worse self-esteem insight was associated with not only suicide ideation/attempt but also with activity reduction and psychomotor retardation. Worse symptom insight also correlated with psychomotor retardation. Better insight into having an affective disorder was associated with more intense hypochondria symptoms. Finally, worse insight into having an illness was associated with psychotic episodes. Conclusion Our study found that symptoms other than psychosis – suicide ideation, psychomotor retardation and reduction of activity and work – correlate with insight impairment in bipolar depression.